EFFECT OF LAND DEGRADATION ON SMALLHOLDERS FARMERS’ FOOD SECURITY AND POVERTY STATUS NEXUS LIVELIHOOD DIVERSIFICATION IN NORTH CENTRAL, NIGERIA - Yusuf Usman Oladimeji; Yusuf O; Sani A A; Iyanda A S (Socio-Economics/Agribusiness Department, 2020)
The extent of degraded and impoverished lands suitable for agriculture production in Nigeria is highly uncertain and cannot be established without due consideration of current land use and land tenure. The objective of this study was to assess the effect of land degradation on smallholder farmers’ food security and poverty status nexus livelihood diversification in north central Nigeria. Primary data with the aid of structured questionnaire was employed to collect the relevant data. A multistage random farming household survey resulted in five Local Government Areas, eleven villages, 330 farmers which were filtered to 142 and 188 land graded farmers (LDF) and non-degraded farmers (NDF) respectively. Descriptive statistics, land degradation perception index, food security and poverty indices, dichotomous regression models were used to achieve the aims of the study. The result indicates that 86.97% of the sampled farmers identified erosion as the most severe land degradation with perception index of 4.2. Only 12.0% of LDF were food secured while 40.0% of NDF were food secured. The poverty status revealed that only 7.04% of LDF fall under the threshold of 0.00-20.00 category implying non-poor while 46.3% of NDF fall under the threshold. The results showed that the factors that affected food security and poverty status of LDF had variation from those that affected NDF and where it was the same, not by the same magnitude and direction. The average livelihood security composite index of LDF and NDF were 0.27 and 0.64 respectively implying that NDF had a low diversification as value of one means no diversification. The factors influencing livelihood diversification to non-farm activities by LDF and NDF also differs in magnitudes, coefficients and directions. The results revealed that intercropping and mixed cropping are the most common strategy adopted by farmers in mitigating land degradation with mean index of 4.82.